Tensão em madeiras de folhosas: distribuição radial das propriedades e o papel da recuperação higrotérmica - Kugimiya, Tamaki (Universidade Federal de São Carlos, 2025)
In the current era of progressing global warming, the value of forests and wood has been increasing. Trees develop growth stress as a survival strategy to grow tall; however, these stresses become obstacles when humans utilize wood. The elastic component of growth stress is released during felling and sawing, while the viscoelastic component is released during boiling. The latter is referred to as hygrothermal recovery (HTR). Although various studies on HTR have been conducted, its detailed behavior remains unclear. This study aimed to understand the radial distribution of wood properties and the role of HTR in hardwood containing tension wood. In Chapter 3, HTR was examined from the bark to the pith together with the G-layer proportion, crystallinity index (C.I.), microfibril angle (MFA), and drying strain. In Chapter 4, HTR was evaluated under various treatment temperatures and durations, along with drying mass change, crystallite size (L), and d-spacing for comparison. In Chapter 3, the results showed that HTR alone exhibited dependence on the distance from the pith and contributed to the release of the viscoelastic component of growth stress. In Chapter 4, in the tangential (T) direction, viscoelastic release of compressive growth stress was confirmed by detecting the expansion of d-spacing between cellulose molecular chains. In the longitudinal (L) direction, it was confirmed that the viscoelastic release of tensile growth stress likely occurs at a more macroscopic level—such as contractive relaxation of pre-stretched cellulose microfibrils (CMFs)— rather than through a decrease in the d-spacing of cellulose crystallites along the molecular axis. For future studies, analysis using FTIR and small-angle scattering are desirable to elucidate the behavior of the matrix and CMFs during HTR.
Tension in hardwoods: radial property distribution and the role of hygrothermal recovery
Keywords: Recuperação higrotérmica; Madeira tensionada; Estresse de crescimento; Madeira de lei; Hygrothermal recovery; Tension wood; Growth stress; Hardwood; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS; 9. Indústria, Inovação e Infraestrutura